- MANFAAT ECOPRINT SEBAGAI TERAPI SENI UNTUK MELATIH FUNGSI KOGNITIF BAGI LANSIA - Dewi Isma Aryani; Monica Hartanti; Arimbi Putri; Hendra Setiawan (Universitas Negeri Surabaya, 2023)
Universitas Kristen Maranatha is a private university in Bandung with a work program based on the ICE principles of integrity, care, and excellence in the disciplines of teaching, research, and community service, with one of them focusing on social problems. So far, lecturers from various study programs have collaborated with partners from the Yayasan Indonesia Ramah Lansia in West Java Province to develop materials relevant to ecoprint training for the elderly. The goal of this exercise is to provide the elderly an understanding of the ecoprint process as an art therapy tool for improving cognitive function. Art plays a significant role in this activity since it is a sort of creative activity that keeps the elderly engaged and productive in their latter years. The exercise took place in the Seroja Elderly School in Cinambo, Bandung. It is believed that by participating in this activity, the elderly would be able to put the insights and ecoprint techniques they have learned to use to train their cognitive skills to stay in excellent shape.